2016
DOI: 10.1136/bmjopen-2015-010963
|View full text |Cite
|
Sign up to set email alerts
|

Competence of health workers in emergency obstetric care: an assessment using clinical vignettes in Brong Ahafo region, Ghana

Abstract: ObjectivesTo assess health worker competence in emergency obstetric care using clinical vignettes, to link competence to availability of infrastructure in facilities, and to average annual delivery workload in facilities.DesignCross-sectional Health Facility Assessment linked to population-based surveillance data.Setting7 districts in Brong Ahafo region, Ghana.ParticipantsMost experienced delivery care providers in all 64 delivery facilities in the 7 districts.Primary outcome measuresHealth worker competence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…In conclusion, we provided evidence that facility birth alone, in a setting with low facility capability 40 and provider skill, 41 does not confer any survival benefit for women or babies. Encouraging women to deliver in facilities that are unable to safely manage routine deliveries and complications might actually cause harm and be unethical 12, 60.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In conclusion, we provided evidence that facility birth alone, in a setting with low facility capability 40 and provider skill, 41 does not confer any survival benefit for women or babies. Encouraging women to deliver in facilities that are unable to safely manage routine deliveries and complications might actually cause harm and be unethical 12, 60.…”
Section: Discussionmentioning
confidence: 68%
“…Of the 64 facilities offering childbirth care, 24 were classified as capable of providing high-quality routine care, 12 as capable of providing emergency obstetric care (EmOC), of which eight were capable of providing CEmOC, and five were capable of providing emergency newborn care (EmNC) 40 . Detailed information on methods and findings of this comprehensive health facility assessment have been published elsewhere 40, 41. Briefly, we used information on key signal functions, availability of drugs, equipment, and trained health professionals to create quality scores of different dimensions of care, including routine childbirth care, CEmOC, and EmNC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance and quality were also modelled in several alternative ways (see supplementary files ): distance to the closest facility of a certain quality level (using categorization as described above) and the highest quality facility within a certain distance. Furthermore, two alternative quality measures were evaluated: a simple score counting one point per signal function, per doctor conducting cesarean sections (up to 3) and per health professional (up to 3) at each facility (total maximum 32 points), and health worker competence as evaluated with two clinical vignettes (total maximum 20 points, for details see 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Ghana, Lohela, Nesbit, Manu et al (28), have indicated that, apart from medical doctors, midwives are the most capable professionals at providing su cient quality emergency obstetric and neonatal care.…”
Section: Introductionmentioning
confidence: 99%